INTERACTIVE WEB 2.0 TOOLS IN CONTENT AND LANGUAGE INTEGRATED LEARNING - Rinata R. Zaripova; Leila L. Salekhova; Andrew V. Danilov (Высшее образование в России)
Abstract. This study reveals the process of using interactive Web 2.0 tools in CLIL (Content and Language Integrated Learning) classrooms. In modern conditions teachers have to work in multilingual classes, where the most of students are bilinguals. Researchers develop various models of bilingual education that have their own specifics related to the historic, linguistic, social, ethnic, economic situation. During the past 20 years the Content and Language Integrated Learning, or CLIL, is becoming increasingly widespread as a bilingual educational approach around European Union. It means that the second language is used as the medium of instruction in a process of teaching various subjects. In this research we describe the linguistic situation in the Republic of Tatarstan. The majority of secondary school graduates that use Tatar language as a medium of instruction meet with cognitive and linguistic difficulties when they begin studying at the university, where Russian is mostly used. Thus, it is important to use the CLIL in the higher education system of Republic of Tatarstan. The authors have analyzed the experience of using CLIL in European universities and made the conclusion that the most challenging part of implementation the CLIL methodology is the development of bilingual educational materials. In addition, students and teachers working in a CLIL setting face with a lack of suitable learning materials in the target language for subjects. The aim of present research is to reveal of the impact of using interactive Web 2.0 tools by Tatar-speaking students in the process of Content and Language Integrated Learning (CLIL) implementation while studying ICT. The educational resources for ICT subject were designed and published on the Wikia website, and then the pedagogical experiment was conducted. The duration of the experiment was one semester. In this research we used a convenience sample of 50 first- year students of Tatar Philology and Culture Department of Kazan Federal University. The research was organized and conducted as a pedagogical experiment with parallel groups. Control group was a classical teaching approach group, which consisted of 25 students, in which Russian language was used and only frontal method was applied. Students in the experimental group (25 students) experienced CLIL approach and used appropriate learning materials related to Web 2.0. At the end of the pedagogical experiment, students took part in the final test (post-test). Statistical processing and interpretation of experimental data revealed the positive impact of using the interactive Web 2.0 tools on the process of CLIL implementation by Tatar-speaking students while studying ICT.